(untitled) (Journal of the College of Basic Education, 2023)
Basmala is a standard infinitive of the verb basmala if the person says: In the name of God, the Compassionate, the Merciful or if he writes itThis type of wording is called in the language of carving; It is to abbreviate two or more words into one word.Likewise, Al-Hofla when it is said: There is neither might nor power except with God, and Glory be to Him when it is said: Glory be to God, and so on. The poet said:I smiled at Layla the day after I met herThe Basmala is mentioned at the opening of every surah of the Holy Qur’an. Except for innocence in the Holy QuranWhich the nation unanimously agreed that there is no increase; There is no decrease in it, however, its existence in this way was notSufficient - in a categorical way - in the view of some of them to prove its completion of the Qur’an, especially in the beginning of the surahs, except for Al-Fatihah.There were many studies written about the Basmala; Be it in independent studies. (0; um in booksinterpretation.It is known that the book of interpretation is different in its approaches; I was clearly influenced by grammar studiesthe first; Especially the studies that took the Holy Qur’an as a subject, foremost among which was the Encyclopaedia Al-ThawraBook (The Meanings of the Qur’an) for furs.We have held this research to discuss what was mentioned in this book about the basmalah. Let’s get to a secretThe linguistic lesson remained far from being dealt with due to the large number of close encounters with the Basmala. We hope that we have succeeded in submittingYour new thing serves our eternal language; the language of the Holy Qur’an; God grants success.